COPING STRESS SEBAGAI PEMULIHAN PSIKOLOGIS ANAK USIA DINI AKIBAT PERCERAIAN ORANG TUA - Wicaksono, Falih Akmal Wicaksono; Lidia Sandy Kartika; Mufidah Ch (USRAH: Jurnal Hukum Keluarga Islam, 2025)
This study discusses the influence of husband and wife when carrying out ongoing colonization. The dispute also turned out to be the main cause of divorce in Indonesia, this certainly affects the development of children's mindsets that are still in the process of growing both in mind, characteristics, or mental. This study uses a type of library research (library research) which is carried out by examining library materials or secondary data that focus on the object of research. The results of this study are that children can apply various coping strategies. Focused problem solving, involves active efforts to overcome problems such as seeking social support, or planning solutions. Then it can also be with Emotional focus coping, which can focus on regulating emotions such as trying to forget problems or blaming yourself. Lazaruz and Folkman's theory provides a useful framework for understanding how children cope with stress despite divorce from both parents. This theory identifies various coping strategies such as confrontation, seeking social support, and positive reappraisal.